Efficient biocatalytic synthesis of D-tagatose 1, 6-diphosphate by LacC-catalysed phosphorylation of D-tagatose 6-phosphate. Issue 1 (2nd January 2020) - Schoenenberger, Bernhard; Kind, Stefanie; Meier, Roland; Eggert, Thorsten; Obkircher, Markus; Wohlgemuth, Roland
Abstract: D-tagatose 1, 6-diphosphate is an important metabolite which can be formed via the classical tagatose 6-phosphate pathway or via the tagatose 1-phosphate pathway discovered more recently. The chiral metabolite naturally occurs as an intermediate in the galactose metabolism of various organisms, where it is formed by a reversible condensation of dihydroxyacetone phosphate and D-glyceraldehyde 3-phosphate, whereas D-tagatose 6-phosphate has been synthesized chemically, no chemical synthetic method for further phosphorylation to the D-tagatose 1, 6-diphosphate has been described so far. Therefore, a site-specific biocatalytic phosphorylation of the 1-position in D-tagatose 6-phosphate has been chosen. The lacC gene from Lactococcus lactis subsp. lactis was synthesized, cloned into an appropriate expression vector to allow for the production of LacC, the D-tagatose 6-phosphate kinase in Escherichia coli . Subsequently, an efficient biocatalytic synthesis has been developed for the phosphorylation of D-tagatose 6-phosphate at its C1-position by using the recombinant D-tagatose 6-phosphate kinase and the phosphoenolpyruvate/pyruvate kinase-system for ATP regeneration. This straightforward and scalable one-step biocatalytic synthesis of D-tagatose 1, 6-diphosphate was successfully scaled up to the gram scale. Graphical Abstract: